THE SYNTHESIS OF 4-(4,5-DIPHENYL-1H-IMIDAZOLE-2-YL)-N,N- DIMETHYLBENZENAMINE USING MICROWAVE ASSISTED ORGANIC SYNTHESIS METHOD (MAOS) AS CORROSION INHIBITOR ON CARBON STEEL IN 1% NACL SOLUTION - Asatyas, Syifa
Imidazole derivatives are currently being developed as a corrosion inhibitor in oil and natural gas pipeline. The synthesis method of imidazole derivative 4-(4,5-diphenyl-1H-imidazole-2- yl)-N,N-dimethylbenzenamine was optimized in this study using Microwave Assisted Organic Synthesis (MAOS) method, the resulting compound was then applied as a corrosion inhibitor on carbon steel in corrosive environment 1% NaCl. There was some steps of synthesis in this study, i.e. benzoine condensation, benzoine oxidation to bibenzoil, and formation of imidazole ring. The imidazole ring formation in synthesis of 4-(4,5-diphenyl- 1H-imidazole-2-yl)-N,N-dimethylbenzenamine was caused by reaction between bibenzoil, 4- dimethylamino benzaldehyde, and ammonium acetate in the presence of microwave iradiation for 10 minutes. The resulting compound is a white solid with 61.92% yield, then was characterized by melting point determination, Infrared Spectrofotometry (IR), 1HNMR 13CNMR, and Mass Spectroscopy TOF MS ES . The melting point is 266-267 oC. Mass